2021
DOI: 10.1371/journal.pmed.1003804
|View full text |Cite
|
Sign up to set email alerts
|

Relative risks of adverse events among older adults receiving opioids versus NSAIDs after hospital discharge: A nationwide cohort study

Abstract: Background Although analgesics are initiated on hospital discharge in millions of adults each year, studies quantifying the risks of opioids and nonsteroidal anti-inflammatory drugs (NSAIDs) among older adults during this transition are limited. We sought to determine the incidence and risk of post-discharge adverse events among older adults with an opioid claim in the week after hospital discharge, compared to those with NSAID claims only. Methods and findings We performed a retrospective cohort study using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In accordance with other studies, our study found that falls or fall risk, 16 , 17 , 18 , 19 older age, 20 , 21 , 22 and use of behavioral health services 23 , 24 , 25 , 26 among LOT patients increased the odds of an NEDV. This further emphasizes the need to use risk assessment tools before refilling opioids in older patients, patients at high risk for falls, and those with comorbid depression or anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with other studies, our study found that falls or fall risk, 16 , 17 , 18 , 19 older age, 20 , 21 , 22 and use of behavioral health services 23 , 24 , 25 , 26 among LOT patients increased the odds of an NEDV. This further emphasizes the need to use risk assessment tools before refilling opioids in older patients, patients at high risk for falls, and those with comorbid depression or anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…Research is ongoing to study the efficacy of KTP for treating other animal species, leading to a wider application range of this drug ( Hu et al, 2021 ; Reynolds et al, 2021 ). In addition, the drug is being studied for its use as a safe alternative to opioid analgesics ( Doleman et al, 2021 ; Herzig et al, 2021 ; Pergolizzi et al, 2021 ). Thus, the volumes of production and consumption of KTP will only increase in the future.…”
Section: Occurrence Of Ketoprofen In the Environmentmentioning
confidence: 99%
“…However, administering anaesthesia through a single technique eliminated possible confounders and enabled accurate evaluation of preoperative analgesic efficacy. Although Tramadol is clinically effective, it has been associated with more adverse effects than NSAIDs, particularly nausea and vomiting, limiting its frequent use ( 42 , 43 ). In contrast, NSAIDs have been reported to be less harmful and clinically more effective than opioids.…”
Section: Discussionmentioning
confidence: 99%